Peningkatan Pengetahuan Pembuatan Rangkaian Elektronika Menggunakan Proteus Di SMKN 3 Kota Tegal - Ulil Albab; Qirom Qirom; Dany Sucipto; Rony Darpono; Bahrun Niam (Jurnal Surya Masyarakat, 2025)
This community service activity was initiated in response to the limited ability of students at SMKN 3 Kota Tegal to design and analyze electronic circuits, due to inadequate access to industry-standard simulation software. The purpose of this program was to enhance students’ knowledge and skills through training in electronic circuit development using Proteus software. The implementation method consisted of preparation, training sessions, hands-on practice, and ongoing monitoring and evaluation. Participants included eleventh-grade students from the Electronics Engineering Department and accompanying teachers, who engaged in activities ranging from component introduction, circuit simulation, PCB design, to practical PCB fabrication using CNC machines. Evaluation results indicated a significant improvement in students’ understanding and technical capabilities, evidenced by an increase in average test scores from 75 to 93, and a 133 percent rise in the number of students achieving top score ranges. Furthermore, a shift was observed in teaching methods, from conventional whiteboard instruction to digitally integrated simulations. In conclusion, the Proteus-based training effectively enhanced students’ technical competencies, bridged the gap between theoretical concepts and practical applications, and better prepared vocational graduates to meet the demands of a technology-driven industrial environment..